The five aspect meal model as a conceptual framework for children with a gastrostomy tube in paediatric care. Issue 4 (29th January 2021) - Mårtensson, Ulrika; Jenholt Nolbris, Margaretha; Mellgren, Karin; Wijk, Helle; Nilsson, Stefan
Abstract: Background: Cancer treatments may induce side effects and cause eating problems. A gastrostomy tube may be required in order to maintain and optimise the child's nutritional needs. Despite the use of a gastrostomy tube, it is important to maintain a natural and attractive mealtime for the child. The Five Aspect Meal Model is age neutral and originally designed to improve restaurant visits. Its five aspects conceptualise what is necessary to ensure a complete meal experience. To date, there is lack of knowledge to guided model development about mealtimes adapted to children and limited knowledge regarding mealtime experiences for children with a gastrostomy tube. Aim: The aim was to investigate whether the Five Aspect Meal Model could be appropriate to be used for children with a gastrostomy tube in caring science and paediatric care. Methods: The design followed steps retrieved from Renjith and colleagues. Seven interviews were performed with the Five Aspect Meal Model as a base in the interview guide. The transcripts were analysed by using a qualitative directed content analysis with a deductive approach, which finally passed into a more inductive one. Findings: All aspects of the Five Aspect Meal Model were represented in the interviews. There were also experiences related to the gastrostomy tube and the mealtimes that did not fit into any of the five predetermined categories. As a result, the modified version was developed, an adapted prescribing practice model that includes seven aspects, whereof bodily discomfort and time for change and acceptance are specific to children with a gastrostomy tube. Conclusion: Based on children and their parent's experiences, the Five Aspect Meal Model has been developed and adapted into a modified version, which includes seven aspects. The modified version seems to be appropriate to use within caring science and paediatric care.